Volatiles of different resistant cotton varieties mediate the host preference of Mirid bug Apolygus lucorum - Wu, Juan; Cao, Yang; Teng, Dong; Shan, Shuang; Geng, Ting; Huang, Xinzheng; Zhang, Yongjun (Frontiers in Plant Science, 2024)
Cotton, a crucial economic crop, is also the preferred host plant of the mirid bug Apolygus lucorum. In our previous field experiments, we found that cotton cultivars Kelin 08-15 and BR-S-10 (healthy and herbivore-damaged plants) exhibit distinct attraction and repellence to A. lucorum, respectively. However, the key plant volatiles determining attraction or repulsion effects remain unknown. Here, we investigated the volatiles emitted by these two cotton cultivars before and after herbivore infestation.We found that susceptible Kelin 08-15 emitted a greater diversity and quantity of volatiles than those of BR-S-10, with herbivore-damdged cottons releasing more volatile substances. Electroantennogram (EAG) recordings further revealed that 15 representative volatiles identified above could elicited electrophysiological responses in female and male A. lucorum antennae. Among them, behavioral assays showed that two compounds, 1,3-Diethylbenzene and 4-Ethylbenzaldehyde, exhibited attractive properties, whereas six volatiles including Hexyl Acrylate, Cumene, 2,4-Dimethylstyrene, Eucalyptol, Linalool and Butyl Acrylate demonstrated repellent effects on A. lucorum. Taken together, our findings suggest the critical role of volatile compounds in mediating bug-plant interactions and provide a foundation for the development of strategies to prevent and control of A. lucorum in cotton fields.